2019
DOI: 10.1136/bmjspcare-2019-001820
|View full text |Cite
|
Sign up to set email alerts
|

Optimised clinical study recruitment in palliative care: success strategies and lessons learned

Abstract: Recruitment challenges to clinical research studies in palliative care settings, particularly in hospices, are well documented. However, a recent study (Hospice Inpatient Deep vein thrombosis Detection (HIDDen) study) performed across five hospices in the UK recruited above target and on time. We describe strategies that aided successful recruitment in this study, and the lessons learnt for improving future studies. A recent review suggested that the ‘Social Marketing Mix Framework’ (SMMF) could help researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This may mean that not all the experiences of those in HPC are considered, and therefore, care models that stem from research may not be appropriate for all types of patients. One way this gap can be remedied is perhaps by establishing/fostering a palliative research network [ 28 , 39 ]. A research network dedicated specifically to palliative care can also help to refine and establish a clearer agenda of research needs [ 34 ].…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
“…This may mean that not all the experiences of those in HPC are considered, and therefore, care models that stem from research may not be appropriate for all types of patients. One way this gap can be remedied is perhaps by establishing/fostering a palliative research network [ 28 , 39 ]. A research network dedicated specifically to palliative care can also help to refine and establish a clearer agenda of research needs [ 34 ].…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
“…Using the 6 P’s of SMM framework provides one potential structure to address these issues. 2 Our findings indicate that the current dosage of one intervention session per week is not sufficient to allow individuals to watch all videos before the caregiving burden becomes too great or the patient dies. Thus, an earlier study enrollment through universal screening is advised for advancing the timing of NOVELA.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to patient/family-related factors, 1 particular obstacles in the hospice setting include lack of research infrastructure, few trained clinical researches, prioritization of clinical responsibilities, lack of protected research time and funding difficulties. 2 As a result, there are few adequately powered hospice clinical trials, especially, studies involving hospice family caregivers (HFCGs). 3 HFCGs, which include spouses, relatives or friends of a patient receiving hospice, are tasked with managing pain and other symptoms at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIDDen study demonstrated the feasibility of recruiting and performing lower limb imaging in hospice/SPCU-based palliative care cancer patients; it recruited ahead of schedule and gained significant ‘buy-in’ from patients and their respective families. 15 …”
Section: Introductionmentioning
confidence: 99%